2020
DOI: 10.1080/08854726.2020.1861536
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the “unknown assailant”: A qualitative exploration with Australian health and aged care chaplains on the impact of COVID-19

Abstract: The global coronavirus pandemic (COVID-19) has brought about physical, psychological and spiritual challenges within health and aged care services across Australia. The aim of this study was to consider the impact of COVID-19 from the perspective of Australian chaplains. Semi-structured interviews were conducted with 17 chaplains. A grounded theory analysis identified three overarching themes: (1) a changing healthcare environment; (2) the impact of the virus; and (3) chaplains responding to the crisis. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Also, Busfield ( 2020 ) described how difficult and challenging it was for chaplains to maintain a calm presence during the first weeks of COVID-19. By contrast, Jones et al ( 2020 ) showed that while chaplains played an important role for hospital patients, their families and healthcare staff, they also need to sustain their spiritual well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Busfield ( 2020 ) described how difficult and challenging it was for chaplains to maintain a calm presence during the first weeks of COVID-19. By contrast, Jones et al ( 2020 ) showed that while chaplains played an important role for hospital patients, their families and healthcare staff, they also need to sustain their spiritual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because although the COVID-19 pandemic has brought spiritual care to the forefront of healthcare and there is growing evidence for the positive role of SCP in the healthcare system during the current healthcare crisis (Busfield, 2020 ; Cadell et al, 2021 ; Drummond & Carey, 2020 ; Dutra & Rocha, 2021 ; Ferrell et al, 2020 ; Harrison & Scarle, 2020 ; Jones et al, 2020 ; Koenig, 2020 ; Murphy, 2020 ; Papadopoulos et al, 2021 ; Peacock, 2020 ; Sarmiento, 2020 ; Swift, 2020 ; Weinberger-Litman et al, 2020 ; Wierstra et al, 2020 ), little is known about the impact of COVID-19 on spiritual care in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, on average, participating chaplains felt their role was neither clear nor unclear to them during the pandemic. Qualitative findings reflected diverging themes in chaplains' experiences such as being seen as unimportant, optional, and being professionally isolated, compared to those who were viewed as essential, well-integrated, and valued in their healthcare institutions' COVID-19 response (Desjardins et al, 2021;Jones et al, 2020;Tan et al, 2021). However, further attention is needed to unpack the complex and interconnected factors that may have underlain and precipitated the state of chaplaincy during COVID-19, such as the roles of hospital administration, chaplain leaders, chaplain practitioners, interprofessional teams, and the larger healthcare delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…A study with chaplains during the first wave of the pandemic in the UK led to a discussion of the importance of pastoral presence for those who are suffering (Swift 2020). Additionally, while noting that the impact of the pandemic in their area was relatively less than in other regions of the world, a few Australian studies have looked at chaplains' experience in aged care during the pandemic, describing adaptations and identifying future issues related to spiritual care (Drummond and Carey 2020;Jones et al 2020;Tan et al 2021). Two international surveys have reached chaplains around the world (some of whom work in aged care) to learn about changes in aspects of spiritual care during the pandemic (Snowden 2021;Vandenhoeck et al 2021).…”
Section: Introductionmentioning
confidence: 99%